Thermal Hydrogen: An emissions free hydrocarbon economy. (27th April 2017) - Moore, Jared
Abstract: Envisioned below is an energy system named Thermal Hydrogen developed to enable economy-wide decarbonization. Thermal Hydrogen is an energy system where electric and/or heat energy is used to split water (or CO2 ) for the utilization of both byproducts: hydrogen as energy storage and pure oxygen as carbon abatement. Important advantages of chemical energy carriers are long term energy storage and extended range for electric vehicles. These minimize the need for the most capital intensive assets of a fully decarbonized energy economy: low carbon power plants and batteries. The pure oxygen pre-empts the gas separation process of "Carbon Capture and Sequestration" (CCS) and enables hydrocarbons to use simpler, more efficient thermodynamic cycles. Thus, the "externality" of water splitting, pure oxygen, is increasingly competitive hydrocarbons which happen to be emissions free. Methods for engineering economy-wide decarbonization are described below as well as the energy supply, carrier, and distribution options offered by the system. Highlights: An energy system named Thermal Hydrogen is proposed to enable deep decarbonization. Thermal Hydrogen utilizes both products of water splitting, hydrogen and oxygen. Hydrogen enables heat/elect. storage while pure oxygen provides "Carbon Capture". The competitiveness of fuel cells using (Thermal) Hydrogen is compared to options. A distribution system that uses existing pipeline infrastructure is envisioned.